Peran Human Capital di Perusahaan - Frendy Wibowo; Chandra Wisnu Utomo (P3M Universitas Aisyiyah Surakarta, 2023)
The aim of this study is to determine the role of human capital in the company. Method used is systematic review through journal reviews regarding human capital in companies Search articles accessed from internet search databases, namely: Emerald, Elsevier, Taylor & Francis, and Google Scholar. The literature review found 5 journals related to human capital: 2 journals with a descriptive design and 3 journals with a quantitative design. The results of the literature review starting from 2016 to 2021 show that 3 journals are from abroad and in English, and 2 journals are from national journals in Indonesian. Results this systematic review shows that human capital has a very important role in the company's human resources. And companies must utilize the human capital they have (knowledge, skills, and values) to advance the interests of the organization. Conclusion this systematic review good company is aware of the fact that employees are the main contributors to profit, providing an opportunity for the company to achieve its goals. Those who work in the core centers of the organization must develop higher skills